Pengenalan Kompos di Sekolah Dasar - Kartini; Degi Alrinda Agustina; Nur Pangesti Apriliyana; Agustinus Toding Bua; Kristiani, Maya (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
Environmental issues, particularly organic waste management, are an urgent global problem that needs to be introduced from an early age. This service activity aims to introduce simple biotechnology through composting to the 5th-grade students of SDN 005 Tarakan City as part of the implementation of the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum. The methods used include a school needs survey, facilitator training, socialisation, and hands-on practice in making compost using organic materials easily found in the school environment. The results of the activity show that students were enthusiastic about participating in the entire series of activities and were able to understand the concept of recycling and the benefits of compost for the environment. Additionally, this activity raises students' awareness of the importance of maintaining environmental cleanliness and provides contextual experiences that support meaningful learning. Composting has proven to be an effective educational medium for fostering environmental awareness, practical skills, and collaborative and socially responsible attitudes in elementary school students.